Creating person-al space for unspoken voices during diagnostic medical imaging examinations: a qualitative study - Chandra Rekha Makanjee; Anne-Marie Bergh; Deon Xu; Drishti Sarswat (BMC, 2021)
Abstract Background There is emerging interest in person-centred care within a short-lived yet complex medical imaging encounter. This study explored this event from the viewpoint of patients referred for an imaging examination, with a focus on the person and their person-al space. Methods We used convenience sampling to conduct semi-structured interviews with 21 patients in a private medical imaging practice in Australia. The first phase of data analysis was conducted deductively, using the six elements of the person-centred, patient-journey framework of the Australian Commission on Safety and Quality in Healthcare: transition in; engagement; decisions; well-being; experience; and transition out. This was followed by inductive content analysis to identify overarching themes that span a patient's journey into, through and out of an imaging encounter. Results The transition-in phase began with an appointment and the first point of contact with the imaging department at reception. Engagement focused on patient-radiographer interactions and explanations to the patient on what was going to happen. Decisions related primarily to radiographers' decisions on how to conduct a particular examination and how to get patient cooperation. Participants' well-being related to their appreciation of gentle treatment; they also referred to past negative experiences that had made a lasting impression. Transitioning out of the imaging encounter included the sending of the results to the referring medical practitioner. Person-al vulnerabilities emerged as a cross-cutting theme. Patients' vulnerability, for which they needed reassurance, pertained to uncertainties about the investigation and the possible results. Healthcare professionals were vulnerable because of patient expectations of a certain demeanour and of pressure to perform optimal quality investigations. Lastly, patients' personal lives, concerns and pressures - their person-al 'baggage' - shaped their experience of the imaging encounter. Conclusion To add value to the quality of the service they deliver, radiography practitioners should endeavour to create a person-al space for clients. Creating these spaces is complex as patients are not in a position to judge the procedures required by technical imaging protocols and the quality control of equipment. A reflective tool is proposed for radiographers to use in discussions with their team and its leaders on improving person-centred care and the quality of services in their practice.